Kant on the human animal : anthropology, ethics, race - Baumeister, David (Book collections on Project MUSE., 2022)
"While Immanuel Kant's account of human reason is well known and celebrated, his account of human animality (Thierheit) is virtually unknown. Animality and reason, as pillars of Kant's vision of human nature, are original and ineradicable. And yet, the relation between them is fraught: at times tense and violent, at other times complementary, even harmonious. Kant on the Human Animal offers the first systematic analysis of this central but neglected dimension of Kant's philosophy. David Baumeister tracks four decades of Kant's intellectual development, surveying works published in Kant's lifetime along with posthumously published notes and student lecture transcripts. They show the crucial role that animality plays in many previously unconnected areas of Kant's thought, such as his account of the human's originally quadrupedal posture, his theory of early childhood development, and his conception of the process of human racial differentiation. Beginning with a delineation of Kant's understanding of the commonalities and differences between humans and other animals, Baumeister focuses on the contribution of animality to Kant's views of ethics, anthropology, human nature, and race. Placing divergent features of Kant's thought within a unified interpretive framework, Kant on the Human Animal reveals how, for Kant, becoming human requires that animality not be eclipsed and overcome but rather disciplined and developed. What emerges is a new appreciation of Kant's human being as the human animal it is."--